The Wood–Ljungdahl pathway as a key component of metabolic versatility in candidate phylum Bipolaricaulota (Acetothermia, OP1). Issue 4 (2nd April 2019) - Youssef, Noha H.; Farag, Ibrahim F.; Rudy, Sydney; Mulliner, Ace; Walker, Kara; Caldwell, Ford; Miller, Malik; Hoff, Wouter; Elshahed, Mostafa
Summary: The Wood–Ljungdahl (WL) pathway is an important component of the metabolic machinery in multiple anaerobic prokaryotes, including numerous yet‐uncultured bacterial phyla. The pathway can operate in the reductive and oxidative directions, enabling a wide range of metabolic processes. Here, we present a detailed analysis of 14 newly acquired, previously analysed, and publicly available genomic assemblies belonging to the candidate phylum Bipolaricaulota (candidate division OP1, and candidatus Acetothermia), where the occurrence of WL pathway appears to be universal. In silico analysis of predicted metabolic capabilities indicates that the pathway enables homoacetogenic fermentation of sugars and amino acids in all three Bipolaricaulota orders (RBG‐16‐55‐9, UBA7950 and Bipolaricaulales). In addition, members of RBG‐16‐55‐9 appear to possess the additional capacity for syntrophic acetate oxidation using the WL pathway; as well as for respiratory growth using oxygen or nitrate. Anabolically, all UBA7950, and the majority of the Bipolaricaulales genomes possess the capacity for autotrophic growth using the WL pathway. Our results highlight the WL‐enabled metabolic versatility in the Bipolaricaulota, emphasize the need for examining the WL pathway in context of the overall metabolic circuitry in uncultured taxa, and demonstrate the value of comparative genomic analysis for providing a detailed overview of metabolic potential in a target microbial lineage and its potential functional niche in an ecosystem.